Risk Factors for Meconium Aspiration Syndrome among the Babies Born Through Meconium-Stained Amniotic Fluid - Gupta, Murli Manohar; K.C., Rajesh; Sah, Shyam Nandan (Journal of Nepalgunj Medical College, 2025)
Introduction: Meconium aspiration syndrome occurs as complications in babies born through meconium-stained amniotic fluid. It presents as early onset respiratory distress mainly seen in the term and near-term infants due to the poor compliance of lungs and hypoxia which may be mild to severe. Acute or chronic hypoxia and/or infection can result in the passage of meconium in utero. Meconium aspiration before or during birth can obstruct airways, interfere with gas exchange, cause respiratory distress. The common risk factors include postdated pregnancy, Hypertensive disease of pregnancy, small for gestational age (SGA), gestational diabetes and maternal drug abuse. Aims: To study the risk factors for meconium aspiration syndrome, and the complications in the neonates born through meconium stained fluid. Methods: TA hospital based cross-sectional study was conducted in the department of pediatrics involving term and post-term inborn neonates born through meconium stained amniotic fluid at Nepalgunj Medical College from November 2024 to May 2025. Results: Total 300 babies were delivered with meconium stained amniotic fluid, among which 40 (13.4%) babies develop meconium aspiration syndrome. Among maternal risk factors for meconium aspiration syndrome premature rupture of membrane was most common and statistically significant, which was seen in 15 (37.5%) cases. Fetal risk factors were non-vigorous baby at birth, need of resuscitation at birth (70%), hypoxic ischemic encephalopathy (30%) and they showed statistically significance. Babies born through meconium-stained amniotic fluid showed respiratory distress as the main complication accounting for 57.5%, followed by sepsis (30%). Among babies who developed meconium aspiration syndrome 35 (87.5%) improved and were discharged, remaining 5 (12.5%) showed no improvement. Conclusion: Maternal risk factors for meconium aspiration syndrome were premature rupture of membrane, prolonged labor, mode of delivery. Nonvigorous baby at birth, need of resuscitation were major risk factors. Respiratory distress was the main complication seen in babies born through meconium-stained amniotic fluid.